Game sides technical-tactical differences between professional male padel players - Ampuero, R.; Mellado-Arbelo, O.; Fuentes-García, J. P.; Baiget, E. (International Journal of Sports Science & Coaching, 2024)
The main objective of this study was to analyze how professional male padel players technically-tactically behave and to whether determine if there are any differences between one game side and the other (left game side, LGS; right game side, RGS). The sample included 12.851 shots corresponding to 8 matches from the quarterfinals, semifinals, and finals of the Premier Padel circuit held in 2022 where 16 different professional right-handed padel male players participated. All matches were analyzed through systematic observation using an ad-hoc instrument. Variables such as, type of strokes, outcomes, hitting zones and switching displacements, were taken into account. Significant differences (p < 0.05) were found on forehands, backhands, backhand volleys, forehand lobs, backhand lobs, counter wall forehand, counter-lateral wall forehand and backhand, and wall descent stroke backhand. Also, significant differences were found regarding the stroke outcomes: into play (RGS 46.4%; p < 0.05); winners (LGS 2.3%; p < 0.01). Finally, significant differences were noticed between switching displacements in which the LGS players switched considerably more times than the RGS (66.7%; p < 0.001). The reported results proved that there exist differences between both game sides regarding their strokes, stroke outcomes, and switching displacements.